Burnout matters: The impact on residential aged care staffs' willingness to undertake formal palliative care training. (April 2015) - Frey, Rosemary; Boyd, Michal; Foster, Sue; Robinson, Jackie; Gott, Merryn
<x content-type="archive" xml:space="preserve">Abstract</x> Introduction Palliative care delivery has become integral to the role of healthcare staff in residential aged care (RAC) internationally. Challenges within this work environment (e.g. workload, staffing levels, resources) may impact on healthcare staffs' willingness to undertake formal palliative care education. The study described herein explored factors (socioenvironmental and psychological) that influence staff willingness to engage in palliative care education. Methods The predictors of palliative care education uptake for healthcare staff (n = 431) from 52 New Zealand RAC facilities in one large urban District Health Board were assessed. Logistic regression was used to explore willingness to engage in education. Results Higher scores for burnout predicted a decreased likelihood of engaging in palliative care education (odds ratio (OR) 0.41, P = 0.01). The identified predictor of willingness to engage in education was previous palliative care experience (OR 1.59, P = 0.027). Discussion These results can inform the design and delivery of future palliative care education programmes within RAC.